Sistema de parqueo inteligente basado en procesamiento de imágenes para optimizar la asignación de espacios vehiculares en parqueaderos públicos. - Zaruma Chariguaman, Anthony Xavier (2026)
This research paper presents the development and implementation of an intelligent parking system based on image processing, whose objective is to optimize the allocation of vehicle spaces in public parking lots. The research was carried out in four phases: analysis of the problem, study and selection of the detection algorithm, system implementation, and evaluation. For the detection of vehicles and available spaces, the MobileNet-SSD algorithm was trained for four weeks, recording parking times before and after its implementation. The system consists of two stages. In the first, computer vision techniques are used to identify free spaces and notify an LED panel, which shows the user the nearest available space. In the second phase, the system detects the entry of vehicles, records the time it takes to park, and automatically updates the LED panel indicating the next free space. This system guarantees efficient and continuous management of vehicle flow. Statistical results show a significant improvement in parking time, reducing the median from 2,275 minutes with the traditional method to 2,010 minutes with the intelligent system, demonstrating the effectiveness of the proposed system in parking management.